Analysis of potential lard adulteration in chocolate and chocolate products using fourier transform infrared spectroscopy - Che Man, Yakoob; Syahariza, Z. A.; Mirghani, Mohamed Elwathig Saeed; Jinab, Selamat; Bakar, Jamilah (Elsevier, 2005)
Fourier transform infrared (FTIR) spectroscopy, in combination with attenuated total reflectance (ATR) and partial least square (PLS) regression, was used to detect the presence of lard in chocolate formulation. The spectral bands associated with lard, cocoa butter and their blends (ranging from 0% to 15% of lard in cocoa butter) were recorded, interpreted and identified. A semi-quantitative approach is proposed to measure the percent of lard in blends on the basis of spectral data at the frequency region 4000–650 cm−1, using the equation y = 0.9225x + 0.5539. The coefficient of determination (R2) was 0.9872 with a standard error (SE) of 1.305. In this paper, the potential of FTIR spectroscopy as a rapid analytical tool for the quantitative determination of adulterants especially lard, in chocolate, is demonstrated.